Comparative genomics of the nuclear and mitochondrial genomes of fungal tree pathogens causing Dothistroma needle blight - Barnes, Irene (University of Pretoria, 2024)
Dissertation (MSc (Bioinformatics))--University of Pretoria, 2024.